Generation of microsecond ytterbium-doped fibre laser pulses using bismuth telluride thin film as saturable absorber - Muhammad Aizi Mat Salim,; Mohd Zulhakimi Ab Razak,; Saaidal Razalli Azzuhri,; Mohd Afiq Ismail,; Fauzan Ahmad,; Sulaiman Wadi Harun, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Bismuth telluride (Bi2Te3), a type of topological insulators, is currently in hot pursuit due to its unique physical properties. Therefore, this paper describes a simple Q-switched Ytterbium-doped fiber laser (YDFL) by using Bi2Te3 thin-film as saturable absorber. The few layers Bi2Te3 film was fabricated using optical deposition technique and subsequently, was used in an all-fiber, YDFL setup. As a result, a self-starting Q-switching pulses were first occurred when the laser pumping power reached 88.6 mW. As the pump power level increased, the observed pulses repetition rates had increased steadily from 17 to 29.63 kHz. Hence, this work demonstrated that Bi2Te3 thin-film can be used to successfully generate Q-switching pulses at 1-micron region and is well suited for many photonic applications operated at this wavelength region.